Edaphic degradation and plant resilience in post-mining calcareous soils within karst landscapes of the Yucatán Peninsula, Mexico. (Revista Ciencia Agraria, 2025)
Limestone extraction in the Yucatán Peninsula has generated highly disturbed landscapes characterized by soil compaction, reduced porosity, and diminished water retention, affecting plant succession and ecosystem resilience. This study compared edaphic properties and vegetation cover across ten sites in Quintana Roo, five impacted by limestone mining and five controls, distributed along the Reforma Agraria–Puerto Juárez highway. Impacted soils exhibited 25% higher bulk density (1.65 vs. 1.32 g/cm³), 27% lower porosity (38.2% vs. 52.6%), and 36% reduced water retention (21.4% vs. 33.7%) compared to controls. Vegetation cover was 46% lower in impacted areas (42.1% vs. 78.5%), with species richness reduced by more than 50% and diversity values significantly lower (H’ = 1.12 vs. 2.34). These findings confirm functional soil degradation that restricts natural recovery in shallow karst environments, where high permeability and limited horizon formation intensify vulnerability to water stress. Edaphic restoration is recommended through organic amendments, structural soil improvement, and enhanced infiltration, complemented by revegetation with native species adapted to thin soils and low water availability. The results provide empirical evidence to guide ecological restoration programs and sustainable management in tropical mining landscapes of the Yucatán Peninsula, strengthening ecosystem resilience and functional soil recovery.
Keywords: soil degradation; plant diversity; , limestone mining; porosity; karst soils